Transmission Network Expansion Planning Considering Line Switching - Meneses, Marco [UNESP]; Nascimento, Edgar; Macedo, Leonardo H. [UNESP]; Romero, Ruben [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
Commonly, in the transmission network expansion planning (TNEP) problem, the objective is to define the minimal-cost investment in new transmission devices, e.g., the transmission lines and transformers, for the system to operate adequately in a planning horizon. In addition to the traditional approach of considering the installation of new components, the presented model considers the enhancement of the system operation performance through the modification of its topology in each operation scenario. This modification is made by switching off the lines that degrade the system's performance. By using an illustrative example, we discuss why congestion is eliminated by switching off specific lines from the system, thereby improving the performance of the existing network and constructed candidate lines and leading to lower investment costs. The proposed method also considers a strategy to reduce the number of lines switched off in order to improve the reliability of the system and avoid alternative optimal solutions with unnecessary lines switched. The tests are carried out using the 46-bus southern Brazilian system and the IEEE 24-bus system, which are usually used as benchmarks for the TNEP problem. The results are compared with the solutions of the traditional model for TNEP to show the efficiency of the proposed approach.
Keywords: Disjunctive model; mixed-integer linear programming; network planning; transmission switching